Reversible mitochondrial uncoupling in the cold phase during liver preservation/reperfusion reduces oxidative injury in the rat model - Petrenko, Alexander; Cherkashina, Daria; Somov, Alexander; Tkacheva, Elena; Semenchenko, Olga; Lebedinsky, Alexander; Fuller, Barry (Elsevier, 2010)
Reversible uncoupling of the mitochondrial electron-transport chain may be one strategy to prevent intracellular oxidative stress during liver cold preservation/warm reperfusion (CP/WR) injury. 2,4-Dinitrophenol (DNP) is a potent water-soluble uncoupling agent for supplementation of the hepatic CP solution. The aim of this work was to investigate the possible influence of DNP in the CP solution on the isolated rat liver state during CP/WR. Livers were subjected to CP at 4 degrees C in sucrose-phosphate based solution (SPS) for 18 h, followed by WR for 60 min in vitro. The final concentration of DNP was 100 microM. DNP presence during the CP stage led to partial ATP level decrease accompanied by a significant diminution in liver TBARS and a prevention of antioxidant enzyme activity decrease (catalase, GSH-PO, GSH-Red) when compared with livers stored without DNP. After DNP wash-out during WR, an improvement in the mitochondrial functional state (higher respiratory control indices and ATP levels, and a decrease in V(4) respiration rates) were observed. This was concurrent with lower TBARS levels, higher antioxidant enzyme activities and significant increase of bile production. The results suggest that reversible uncoupling may be one way to influence oxidative stress associated with hepatic cold preservation.
Keywords: Liver cold preservation/warm reperfusion; 2,4-dinitrophenol; mitochondrial uncoupling; mitochondrial respiration; pro-oxidant/antioxidant state